Analisis Pengaruh Lingkungan Kerja Terhadap Kinerja - Sukardi, Fabianus; Franksiska, Rosaly (Ekuitas: Jurnal Pendidikan Ekonomi, 2020)
The external working environment, the distance to fill the hydrant water stock and the location of the fire are among the factors that constrain the performance of the fire team. There are differences in the results of research on the work environment that affect performance. From the results of research on the work environment there is a positive effect and there is a negative effect. This research was conducted with the aim of examining the effect of the work environment on the performance of the Salatiga City fire fighting team. The sampling technique used Saturation Sampling with the entire population sampled as many as 32 personnel. The data collection methods used interviews and questionnaires, while the analysis tools were simple linear regression. The results of the study prove that the performance environment has a positive and significant effect on the performance of the Salatiga City fire fighting team, indicated by a p-value (0.01) <0.05. This proves that the better the work environment, the better the performance of the Salatiga City fire fighting team, and vice versa.